American Informant - Kassem, Ramzi (Michigan journal of race & law, 2021)
Part of my childhood was spent in Baghdad, Iraq, during the rule of Saddam Hussein. At that time, the regime offered free and universal education and healthcare. Literacy rates in the country surpassed much of the Arabic-speaking world and, indeed, the Global South. As the celebrated Egyptian intellectual, Taha Hussein, famously put it: “Cairo writes; Beirut prints; and Baghdad reads.” Booksellers were everywhere in Baghdad. Its people read voraciously and passionately debated literature, poetry, and a range of other subjects. But what struck me, even as a child, was the absence of sustained talk about politics in bookshops, markets, and other public spaces. I knew that adults could not stay away from the topic of politics in more intimate, private settings, where a deeper level of trust usually reigned. Once you entered the public sphere, however, discretion about politics—and especially local politics—clearly became the better part of valor. Iraqi society had been so thoroughly infiltrated by elements of Hussein’s intelligence services that ordinary people knew to tread with extreme caution. After all, the person standing within earshot at a bustling Baghdad market, overhearing your conversation—or maybe even your direct interlocutor— could be an informant. And the stakes were high: incarceration, torture, or death. That was an early introduction to the valency of informants—their capacity to interact with the society that surrounds them and their distorting effect on it. The lesson has colored my subsequent work on surveillance, including this reflection on the contemporary role of informants in the United States.